2023
DOI: 10.1111/1475-6773.14132
|View full text |Cite
|
Sign up to set email alerts
|

The effects of behavioral health integration in Medicaid managed care on access to mental health and primary care services—Evidence from early adopters

Abstract: Objective: To evaluate the impacts of a transition to an "integrated managed care" model, wherein Medicaid managed care organizations moved from a "carve-out" model to a "carve-in" model integrating the financing of behavioral and physical health care.Data Sources/Study Setting: Medicaid claims data from Washington State, 2014-2019, supplemented with structured interviews with key stakeholders.Study Design: This mixed-methods study used difference-in-differences models to compare changes in two counties that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…We also tested the association of integrated care with measures associated with social determinants of health, including rates of homelessness, arrests, and employment, reflecting the increased interest by states in these measures and the hypothesis that if integration improves overall health, it could translate to improvements in these broader measures of well-being. We conducted separate analyses for (1) enrollees with SMI, (2) enrollees with mild or moderate mental illness (MMI), and (3) enrollees classified as having no mental illness, anticipating that the IMC effort would have heterogeneous associations with these populations . We supplemented the quantitative analyses with qualitative interviews, providing context of the on-the-ground experience of the IMC implementation.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…We also tested the association of integrated care with measures associated with social determinants of health, including rates of homelessness, arrests, and employment, reflecting the increased interest by states in these measures and the hypothesis that if integration improves overall health, it could translate to improvements in these broader measures of well-being. We conducted separate analyses for (1) enrollees with SMI, (2) enrollees with mild or moderate mental illness (MMI), and (3) enrollees classified as having no mental illness, anticipating that the IMC effort would have heterogeneous associations with these populations . We supplemented the quantitative analyses with qualitative interviews, providing context of the on-the-ground experience of the IMC implementation.…”
Section: Introductionsupporting
confidence: 71%
“…A separate study of access measures in IMC focused exclusively on group 1, allowing for 15 quarters (almost 4 years) of postintervention observations. 18 That study found a slight increase in access to primary care (an increase of 2 percentage points from a baseline of 61%) but no changes in access to outpatient mental health services or the use of hospital or ED services for mental health. Our claims data may not be a full representation of all behavioral health encounters during the study period, and…”
Section: Limitationsmentioning
confidence: 84%
See 3 more Smart Citations